MMP-9 Level Comparation between Spontaneous Abortion and Normal Pregnancy - Aloysius Suryawan; Johanes C Mose; Budi Handono (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: Abortion remains a problem in the obstetric care as it is one of the causes of maternal and fetal death. Bleeding or miscarriage threat in the first trimester comprises 20% to 25% of all pregnant women, and 50% of them will end as spontaneous abortion. The major cause of maternal death in abortion is hemorrhage. Some recent studies have indicated that MMP-9 is important in the process of embryo implantation into the endometrium and spontaneous abortion occurs when there is an overwhelming increase of MMP-9. This data indicate the importance of a further research to elucidate the role of MMP-9 in spontaneous abortion.METHODS: This was a cross sectional study, included 70 pregnant women with gestational age <20 weeks who came for examination and treatment at the Department of Obstetrics and Gynecology, Medical Faculty of Padjadjaran University/Hasan Sadikin Hospital, Bandung. RESULTS: There were differences in the MMP-9 levels in spontaneous abortion compared to normal pregnancy and MMP-9 had a cut-off point >1221.7 with the sensitivity of 48.6% specificity of 80%, and accuracy of 60.9%.SUMMARY: The MMP-9 level in spontaneous abortion was higher than in normal pregnancy.KEYWORDS: MMP-9, spontaneous abortion, normal pregnancy